Editor's Introduction - De Giorgi, Alessandro (Social justice, 2015)
An introduction is presented in which the editor discusses various reports within the issue on topics including the discursive field on the U.S. prison crisis, penal reforms in the U.S. as part of a broader radical-reformist agenda, and an analysis of the growing opposition to mass incarceration.